An overview on clinical, pathological and molecular features of lung metastases from colorectal cancer. (3rd July 2019) - Procaccio, Letizia; Bergamo, Francesca; Manai, Chiara; Di Antonio, Veronica; Fassan, Matteo; Zagonel, Vittorina; Lonardi, Sara; Loupakis, Fotios
ABSTRACT: Introduction : Lung metastases occur in 10–20% of patients with colorectal cancer (CRC). Most of them are treated with palliative intent and have a poor prognosis. Pulmonary metastasectomy may be a curative option for carefully selected patients with 5-year survival rates ranging from 25% to 60%. However, up to 70% of patients develop recurrence after pulmonary metastasectomy. Therefore, the identification of prognostic factors is essential in CRC patients with resectable lung metastases. Areas covered : This review aims at summarizing the actual body of knowledge available on lung metastases from CRC focusing on their clinical, pathological and molecular profile. Moreover, we provide an update on experts' attitudes towards lung metastasectomy, adjuvant or perioperative chemotherapy. Expert opinion : Traditional clinical prognosticators such as the total number of pulmonary metastases, carcinoembryonic antigen (CEA) serum levels before surgery, and presence of lymph node metastases cannot provide reliable criteria to predict survival after lung metastasectomy. Indeed, research efforts have been directed in recent years toward studying the biological characteristics of lung lesions to better define prognosis and response to treatment, and ultimately shed new light on their proper local and systemic management.